EDUKASI PEMANFAATAN SARI BUAH TOMAT SEBAGAI SEDIAAN MASKER DI SMA SWASTA HARAPAN 1 KOTA MEDAN - Marbun, Nova rianti; Sari, Sofia Elia; purba, jhan saberlan; Sembiring, Tio Ranti Sari (INSTITUT KESEHATAN DELI HUSADA, 2025)
Community Service aims to increase public knowledge and understanding regarding the use of tomato juice as a basic ingredient for natural cosmetic preparations. Tomatoes (Solanum lycopersicum) are known to contain various active substances such as lycopene, vitamin C, and antioxidants that are beneficial for skin health, including brightening, moisturizing, and protecting against free radicals. Educational activities are carried out through counseling, forcing the preparation to be made, and distributing leaflets to the target community. The results of the activities showed a significant increase in participants' knowledge regarding the benefits and how to make cosmetic preparations based on tomato juice. This program is expected to encourage the community to make more use of natural ingredients in skin care and reduce dependence on chemical products.